2019
DOI: 10.1177/0954407019830205
|View full text |Cite
|
Sign up to set email alerts
|

Research and analysis of the wheeled vehicle load spectrum editing method based on short-time Fourier transform

Abstract: The measured uniaxial-head load spectrum in the road simulation test has a large number of useless small loads. When applying the measured load spectrum directly, it will take a lot of time. This paper designs a comprehensive road spectrum measurement system to collect data and proposes a method for editing the uniaxial-head acceleration load spectrum using short-time Fourier transform to speed up the reliability test process and reduce time costs. In this method, the time domain and frequency domain informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The STFT-based editing process is with reference to [ 12 ]. Combined with a ‘spectrogram’ function in MATLAB, the window function is chosen as the Gaussian, with a window length and an overlap .…”
Section: Load Signals Acquisition and Accelerated Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…The STFT-based editing process is with reference to [ 12 ]. Combined with a ‘spectrogram’ function in MATLAB, the window function is chosen as the Gaussian, with a window length and an overlap .…”
Section: Load Signals Acquisition and Accelerated Editingmentioning
confidence: 99%
“…The Short-time Fourier-transform (STFT) based approach divides the load spectrum into a series of equal-length short segments, and then Fourier-transforms of each segment are adopted to express the load history in the time-frequency domain [ 10 ]. Pratumnopharat et al [ 11 ], Liu et al [ 12 ], and Wen et al [ 13 ] successively investigated various fatigue data editing methods, where the accumulative power spectral density (AccPSD) of the signal obtained by STFT was proposed to identify fatigue damage events. The results indicated that the STFT-based method could not only improve the accuracy of fatigue damage retention but also shorten time durations.…”
Section: Introductionmentioning
confidence: 99%
“…The load spectrum expresses the load time history of components in the real working condition, that is, the statistical law of load and time, which is widely used in aerospace [3][4], automobile [5][6], mechanical engineering [7] and other fields. Compiling the load spectrum of motorized spindle provides the basis to simulate the actual working conditions in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the applicability of the shortened signal, this kind of signal can be normally used in laboratory scale durability fatigue test. Liu et al 22 applied the STFT method for editing the measured uniaxial-head acceleration load spectrum in the road simulation test to speed up the reliability test process and reduce time costs. Wen et al 23 applied the STFT approach to identify and extract high fatigue damage segments of original load signal and obtain reduced accelerated load spectrum of tractor components.…”
Section: Introductionmentioning
confidence: 99%